INFECTIOUS DISEASES OF THE CENTRAL NERVOUS SYSTEM MENINGITIS (Conferencea, 2022)
Meningitis is an acute inflammation of the soft membranes of the head and spinal cord. Meningitis is mainly an infectious disease.